L'impact de l'homophobie et de la violence homophobe sur la persévérance et la réussite scolaires - Chamberland, Line; Émond, Gilbert; Julien, Danielle; Otis, Joanne; Ryan, William (Ministère de l'Éducation, du Loisir et du Sport (MELS)/Fonds Québécois de la recherche sur la société et la culture (FQRSC), 2015)
Plus du tiers (38,6%) des 2747 élèves du secondaire sondés dans le cadre de cette étude rapportent avoir été victimes d’au moins un acte de violence en milieu scolaire, parce qu’ils sont ou parce qu’on pense qu’ils sont lesbiennes, gais, ou bisexuel-les (LGB). Au collégial, 4,5% des répondant-es rapportent avoir vécu de la violence homophobe. Ces résultats de la recherche "Impact de l’homophobie et de la violence homophobe sur la persévérance et la réussite scolaires" (Line Chamberland, chercheure principale, UQAM) révèlent que la violence à caractère homophobe n’est pas uniquement le lot d’une minorité d’élèves LGB, mais bien d’une grande proportion d’élèves, sans égard à leur orientation sexuelle, à leur sexe, à leur langue d’origine, à leur lieu de naissance ou de scolarisation, ou encore à leur niveau scolaire. Cette recherche, menée en collaboration avec des chercheur-es des universités UQAM, Concordia et McGill, visait à dresser le portrait du climat scolaire des écoles secondaires et des établissements collégiaux du Québec, en lien avec l’homophobie, ainsi qu’à étudier les impacts de la violence homophobe sur le cheminement scolaire des jeunes de minorités sexuelles qui en sont ou en ont été victimes. Dans un premier temps, un questionnaire sur l’homophobie et l’homosexualité en milieu scolaire a été rempli par des élèves de niveau secondaire 2e cycle (n=2747) et de niveau collégial (n=1844). Des entrevues ont également été menées, individuellement ou en groupe, auprès de 73 jeunes de 14 à 24 ans s’identifiant comme lesbiennes, gais, bisexuel-le-s ou en questionnement (LGBQ), provenant de familles homoparentales (F) ou s’identifiant comme transsexuel-les (T). Les questions d’entrevue portaient sur leurs expériences scolaires et personnelles en lien avec leur orientation sexuelle (ou celle d’un parent) et/ou leur identité de genre.
Keywords: 2000 à aujourd'hui; 2000-2009; EDI; LGBTQIA2+; amérique du nord; amériques; canada; formations; homophobie; identités LGBTQIA2+; outils; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; violences

Taire ou exposer la diversité sexuelle ? Impacts des normes de genre et de l'hétéronormativité sur les pratiques enseignantes - Richard, Gabrielle (Genre, sexualité & société, 2015)
À partir de 22 entretiens et de 243 questionnaires d’enquête complétés par des enseignants du secondaire du Québec (Canada), cet article interroge l’existence de normes relatives au genre et à l’orientation sexuelle en milieu scolaire. Les résultats suggèrent que les pratiques professionnelles des enseignant(e)s, tant lesbiennes, gais et bisexuels (LGB) qu’hétérosexuel(le)s concernant l’homophobie et la diversité sexuelle sont influencées par ces normes. Trente ans après les premiers travaux sur le vécu des enseignants LGB, la littérature sur le coming out demeure centrale pour comprendre les pratiques professionnelles de ceux-ci ainsi que leurs appréhensions. Based on 22 interviews and 243 survey questionnaires filled out by high school teachers in Québec (Canada), this paper questions the existence of norms relating to gender and sexual orientation in schools. Results suggest that teachers’ professional practices regarding homophobia and sexual diversity are influenced by these norms, whether they identify as heterosexual or as lesbian, gay or bisexual (LGB). Thirty years after the first studies on LGB teachers’ experiences, the coming out literature remains central to the understanding of teachers’ apprehensions and fears, as well as their pedagogical practices.
Keywords: EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; diversité sexuelle; homophobie; hétérosexisme; identités LGBTQIA2+; québec; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; école secondaire; étude qualitative; étude quantitative

The pedagogical practices of Québec high school teachers relative to sexual diversity - Richard, Gabrielle (Journal of LGBT Youth, 2015)
This article explores the ways in which teachers describe their pedagogical and intervention practices relative to sexual diversity in Québec (Canada). Three variables closely associated with teachers who report inclusive practices emerge: experiential training (based on the experience of a lesbian, gay, or bisexual [LGB] teacher), contact training (from close acquaintance with LGB individuals), and professional training. These factors impact the probability that a teacher will refer to homosexuality, intervene when homophobic incidents occur to deconstruct prejudices, and become the confidant of LGBQ students. Results are discussed based on research on minority teachers and on the roles of straight allies in education.
Keywords: EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; diversité sexuelle; formations; homophobie; hétérosexisme; identités LGBTQIA2+; outils; québec; ressource en ligne; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; école secondaire

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

"Why Should Our Bodies End at the Skin?": Embodiment, Boundaries, and Somatechnics - SHILDRICK, MARGRIT (Hypatia, 2015)
Donna Haraway's enduring question—"Why should our bodies end at the skin?" (Haraway 1990, 220)—is ever more relevant in the postmodern era, where issues of bodies, boundaries, and technologies increasingly challenge not only the normative performance of the human subject, but also the very understanding of what counts as human. Critical Disability Studies has taken up the problematic of technology, particularly in relation to the deployment of prostheses by people with disabilities. Yet rehabilitation to normative practice or appearance is no longer the point; instead, the lived experience of disability generates its own specific possibilities that both limit and extend the performativity of the embodied self. I look at what is at stake in the challenge to the Western logos that comes specifically from the capacities of the disabled body, understood not as a less than perfect form of the normative, but as figuring difference in a nonbinary sense. Feminist theory has long contested the isomorphism of the logos, but I go beyond simply setting out the grounds for revaluing multiple variant forms. The feminist turn to Jacques Derrida and Gilles Deleuze opens up the problematic to a celebratory positioning of difference and transcorporeality as the very conditions of life.
Keywords: EDI; approches et analyses; arts; bioéthique; corps; cours; discipline; philosophie; postmodernisme; premier cycle; prothèses; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; technologie; thématiques; études critiques du handicap; études littéraires